Multi-agent distributed adaptive resource allocation (MADARA). (1st September 2010) - Edmondson, James; Schmidt, Douglas
The component placement problem involves mapping a component to a particular location and maximising component utility in grid and cloud systems. It is also an NP hard resource allocation and deployment problem, so many common grid and cloud computing libraries, such as MPICH and Hadoop, do not address this problem, even though large performance gains can occur by optimising communications between nodes. This paper provides four contributions to research on the component placement problem for grid and cloud computing environments. First, we present the multi-agent distributed adaptive resource allocation (MADARA) toolkit, which is designed to address grid and cloud allocation and deployment needs. Second, we present a heuristic called the comparison-based iteration by degree (CID) heuristic, which we use to approximate optimal deployments in MADARA. Third, we analyse the performance of applying the CID heuristic to approximate common grid and cloud operations, such as broadcast, gather and reduce. Fourth, we evaluate the results of applying genetic programming mutation to improve our CID heuristic.